THE MAIN TRENDS IN SMALL-TOWN PLANNING AND DEVELOPMENT IN THE MIDDLE IRTYSH REGION IN THE SOVIET PERIOD - Sokolova,; Gefner,; Yudina, (Revista Inclusiones, 2019)
The article looks at the main trends in small-town planning and development in the Middle Irtysh region in the Soviet period. The source base of the research is represented by a variety of different sources, including sources that are non-conventional for historical studies (“visual texts”). Comprehensive analysis of sources has allowed the authors to study the problem in a detailed and multifaceted way. Specific features of the source base, as well as the subject and objective of the research, have determined the scope of essential tools employed including the conventional principles and methods used in historical studies, as well as practices of new local history that are being actively implemented at the present time. In the course of the research, the authors paid close attention to the factors that shaped the town planning and development process and its main vectors. In their opinion, the primary factor was the national policy in the sphere of urban planning, public services, and amenities. The historical past of towns, the lifestyle of their inhabitants and specific features of business activities have also influenced the processes under examination.